If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2x-4)=36
We simplify the equation to the form, which is simple to understand
6(2x-4)=36
Reorder the terms in parentheses
+(+12x-24)=36
Remove unnecessary parentheses
+12x-24=+36
We move all terms containing x to the left and all other terms to the right.
+12x=+36+24
We simplify left and right side of the equation.
+12x=+60
We divide both sides of the equation by 12 to get x.
x=5
| 5x-(3x-4)=17 | | 4x^2-28x+11=0 | | 6(13-2x)=50-x+46 | | 0+11y=7 | | 0+11y=y | | 2(4x+3)=12x+4-4x+2 | | 3(2x-1)+2(x+3)=3(x-2)-2(x-1) | | x^2-13x+24=0 | | 12x-7=1+10x | | -7=-y+4 | | x+(x-3007)=7803 | | X=0+4 | | 250=84-5(x-4) | | 5+8q=7+7q | | -5y-3=1-6y | | X^2+x+0.21=0 | | 4(x-2)=x-8+3x | | 12x+6-10x=2x+6 | | (n-2)*5=20 | | 22a+5-(a-7)=48 | | x(x-2)+(x-2)(x+2)=0 | | 2-.75k=.125k+9 | | 4(x+2)=5-(x+2) | | 10(9c-1)-14=88c+10 | | 3x+-3+5=5 | | 4(x+2)=5-(x-2) | | 0.6(x-2)=12.0 | | 8x+8-5x=3x+8 | | 7n=77 | | 12x-3=90+3(x-7) | | n-12=10 | | 3x+4=6-7x |